PENGARUH DAYA TARIK PROMOSI, KEMUDAHAN PENGGUNAAN, DAN KEAMANAN TERHADAP MINAT PENGGUNAAN E-MONEY PADA MAHASISWA POLITEKNIK NEGERI SEMARANG - Putri, Cynthia Syerin Perdana; Handayani, Jati; Agustinus, Tribekti Maryanto (Finance and Banking Program, Accounting Department, Politeknik Negeri Semarang, 2021)
The purpose of this study is to analyze the effect of promotional attractiveness, user-friendliness, and security on the interest in using e-money either simultaneously or partially in Semarang State Polytechnic students. The population of this study were all Semarang State Polytechnic students. The sample selection method used convenience sampling with 100 respondents in this study. The data were analyzed using multiple linear regression with the help of SPSS 25. The results of this study indicate that simultaneously or partially promotional attractiveness, ease of use, and security have a significant effect on interest in using electronic money among Semarang State Polytechnic students. It shows that promotions are carried out to attract students, ease of use and security attract users to switch to e-money especially in the digital era